INTEGRATION BETWEEN THE MUNICIPAL HEALTH COUNCIL AND SOCIETY: CHALLENGES AND PATHS WITHIN THE SUS FRAMEWORK (Editora Impacto Científico, 2025)
Social participation is one of the fundamental pillars of the Unified Health System (SUS) in Brazil, structured on the basis of decentralization, universalization and social control. The Municipal Health Councils represent strategic spaces for dialogue between the state and civil society, promoting public policies that are more legitimate and adherent to local realities. However, these councils face challenges such as structural limitations, low training, popular demobilization and political-institutional influence, which compromises their representativeness and autonomy. Strengthening these spaces requires investment in ongoing training, accessible communication, intersectoral coordination and the inclusion of historically marginalized groups. In addition, it is essential to guarantee material conditions that allow for effective participation and to create mechanisms for continuous monitoring and evaluation. The article argues that the consolidation of social participation in the SUS is directly related to the promotion of democracy, equity and human rights, highlighting the role of councils as catalysts for social transformation and active citizenship.